Unpacking climate effects on boreal tree growth : An analysis of tree-ring widths across temperature and soil moisture gradients - Lundgren, Andreas; Strengbom, Joachim; Edvardsson, Johannes; Granath, Gustaf (Biogeosciences, 2025)
The effect of climate change on tree growth in boreal forests is likely mediated by local climate conditions and species-specific responses that vary according to differences in traits. Here, we assess species-specific tree growth responses to climate along gradients of mean annual temperature and soil moisture. We assessed growth-climate relationships by using tree-ring width data in Norway spruce (Picea abies) and Scots pine (Pinus sylvestris) from the Swedish National Forest Inventory in relation to climatological data along gradients in mean annual temperature and soil moisture. Trees growing in warmer areas responded more negatively to high temperature and more positively to high precipitation. Site-specific soil moisture only showed an effect on the growth responses in areas of high mean annual temperature. The growth-climate response differed between the species; specifically, the growth response to high temperature varied more along the gradient of mean annual temperature for P. abies than for P. sylvestris. Growth responses to extreme weather events did not deviate from non-extreme events along the climatic gradients. Our study suggests that tree growth responses to climate change will depend on tree species and site-specific climate conditions. In warmer areas, high soil moisture may mitigate the adverse effects of warming on tree growth mainly for P. abies. In colder areas, P. abies is likely to benefit more from warming than P. sylvestris. Although the matching between extreme tree growth and extreme temperature or precipitation years was consistently higher than expected if the two variables were independent, an extreme year is unlikely to cause a tree growth response that markedly diverges from predictions based on linear relationships. Thus, the amplification of negative growth-climate responses during extreme years is likely of limited importance for long-term growth, as such events are inherently rare. Nevertheless, extreme years may influence forest productivity by affecting tree mortality, an aspect that was beyond the scope of this study. In the face of climate change, our results emphasize that forest management should consider site-specific climate conditions and species differences to sustain future forest productivity.
Publisher Copyright: © Copyright: